Novinky v oblasti perioperační nutriční podpory - Awad, Sherif; Lobo, Dileep N (Current Opinion in Anesthesiology, 2011)
To highlight recent developments in the field of perioperative nutritional support by reviewing clinically pertinent English language articles from October 2008 to December 2010, that examined the effects of malnutrition on surgical outcomes, optimizing metabolic function and nutritional status preoperatively and postoperatively. RECENT FINDINGS: Recognition of patients with or at risk of malnutrition remains poor despite the availability of numerous clinical aids and clear evidence of the adverse effects of poor nutritional status on postoperative clinical outcomes. Unfortunately, poor design and significant heterogeneity remain amongst many studies of nutritional interventions in surgical patients. Patients undergoing elective surgery should be managed within a multimodal pathway that includes evidence-based interventions to optimize nutritional status perioperatively. The aforementioned should include screening patients to identify those at high nutritional risk, perioperative immuno-nutrition, minimizing 'metabolic stress' and insulin resistance by preoperative conditioning with carbohydrate-based drinks, glutamine supplementation, minimal access surgery and enhanced recovery protocols. Finally gut-specific nutrients and prokinetics should be utilized to improve enteral feed tolerance thereby permitting early enteral feeding. SUMMARY: An evidence-based multimodal pathway that includes interventions to optimize nutritional status may improve outcomes following elective surgery.
Keywords: Patients; předoperační péče; Nutritional Status; Immune System; Recovery of Function; Humans; lidé; perioperační péče; obnova funkce; nutriční stav; Nutritional Support; Malnutrition; Preoperative Care; podvýživa; Perioperative Care; Postoperative Care; nutriční podpora; pacienti; pooperační péče; imunitní systém; Postoperative Period; pooperační období